2019
DOI: 10.1007/s12298-019-00732-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic assessment of the internal transcribed spacer region (ITS1.2) in Mangifera indica L. landraces

Abstract: Mango (Mangifera indica) is one of the most important tropical fruits in the world. Twenty-two genotypes of native mangoes from different regions of southern Iran (Hormozgan and Kerman) were collected and analyzed for the ribosomal genes. GC content was found to be 55.5%. Fu and Li's D* test statistic (0.437), Fu and Li's F* test statistic (0.500) and Tajima's D (1.801) were positive and nonsignificant. A total of 769 positions were identified (319 with insertion or deletion including 250 polymorphic and 69 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This result was similar to Hidayat et al 9 when separating mango varieties collected from different countries Malaysia, India, Indonesia, Thailand, Taiwan into 3 different groups based on ITS region. The ITS sequence also exhibited high diversity in DNA sequence characteristics and can be effectively applied in the molecular identification of native mangoes in Southern Iran 26 . Even with high diversity, we found that the genetic similarity of intra-genetic samples based on ITS was not affected by the geographical sampling sites.…”
Section: T G G C G C T C T G G G C C G a G G T G C T G G G G T G Amentioning
confidence: 99%
“…This result was similar to Hidayat et al 9 when separating mango varieties collected from different countries Malaysia, India, Indonesia, Thailand, Taiwan into 3 different groups based on ITS region. The ITS sequence also exhibited high diversity in DNA sequence characteristics and can be effectively applied in the molecular identification of native mangoes in Southern Iran 26 . Even with high diversity, we found that the genetic similarity of intra-genetic samples based on ITS was not affected by the geographical sampling sites.…”
Section: T G G C G C T C T G G G C C G a G G T G C T G G G G T G Amentioning
confidence: 99%
“…is sister to subclade of H. tuberculatum and H. blanchei. ITS 1 and ITS2 are widely used in plant phylogenetic studies due to their ability to teasing out the intra-and interspecific variation among species [10]. In general, the base substitutions in the ITS region among Haplophyllum species are more than other species in angiosperm [2].…”
Section: Resultsmentioning
confidence: 99%
“…However, few species have been identified or studied through molecular approaches [2]. Nuclear ribosomal internal transcribed spacer (ITS) regions are more powerful than other plastid regions in identification of intraspecific variability among species of the same genus [10][11][12]. ITS regions are characterized as ITS1 and ITS2.…”
Section: Introductionmentioning
confidence: 99%
“…ITS is a degraded region during maturation in ribosomal transcript. (Choudhary et al, 2015) ITS due to more variation properties than ribosomal sequences have been commonly used for molecular markers to figure out phylogenetic analysis and/or identification of bacteria, plant and animal strains and/or species (Lee et al, 2017;Rocha et al, 2019;Ali et al, 2019;Fazeli-Nasab et al, 2020). Pourahmad et al (2019) performed sequence analysis of the mycobacterial 16S-23S ITS region to determine aquatic mycobacteria species, reporting effectiveness of this marker.…”
Section: Its (Internal Transcribed Spacer)mentioning
confidence: 99%